Judicial Silence on Administrative Malpractice: The Disregard of Notarial Repertorium in the Legal Considerations of Indonesian Supreme Court Decisions - Budiman, Firdaus Charisma; Sudarwanto, Albertus Sentot; Ismunarno, Ismunarno (CV. Social Politic Genius (SIGn), 2025)
The legitimacy of the Civil Law Notary system in Indonesia hinges on the integrity of state protocol, which serves as the absolute guarantor of deed authenticity. However, this idealism frequently crumbles due to judicial pragmatism that disregards procedural defects in administrative proceedings. This research aims to deconstruct the judicial reasoning anomaly in Decision Number 1859 K/Pdt/2015, in which the Supreme Court Justice annulled a notary deed without expounding on the violation of the Repertorium obligation as the basis for legal consideration. Employing a doctrinal legal research method that applies the critical examination of judicial reasoning, this study dissects the Supreme Court Justice’s logical flow and juxtaposes it with the legal fact of the novum regarding the empty Repertorium book. Through the analytical lens of Austin’s Legal Positivism Theory, this research finds that the disputed deed constitutes a “Phantom Deed” that violates the sovereign’s command. Crucial findings indicate that the Supreme Court Justice committed judicial silence as a form of disregard toward the violation of Article 58 of Law Number 30 of 2004 in their ratio decidendi. The Justice opted for a judicial shortcut to annul the deed on the basis of downstream land certificate defects, yet remained silent on upstream administrative malpractice. This study concludes that the decision represents a “right decision, wrong reasoning,” which systemically undermines the judiciary’s educational function and obscures the standard of notarial professional liability in maintaining national legal certainty.